Relationship between university students’ physical activity and mobile phone dependence: Mediating effect of subjective well-being and moderating effect of psychological capital - Lu, Tianci; Wang, Caixia; Chen, Hanwen; Tao, Baole; Jiang, Yueyan; Sui, Haoran; Yan, Jun (Frontiers in Psychology, 2022)
Background: With the ongoing development of the information society, the Internet and smartphones have become an essential way of life, but also fostered the problem of mobile phone dependence. Physical activity and subjective well-being have both been shown to correlate with mobile phone dependence, but the impact of subjective well-being on the relationship between physical activity and mobile phone dependence is not fully understood. This study investigates subjective well-being as a potential mediating variable in the relationship. It also investigates whether psychological capital moderates the association between subjective well-being and mobile phone dependence. Methods: A total of 9,569 students from 38 universities in Jiangsu Province were selected. Participants were surveyed via the online questionnaire distribution platform Questionnaire Star. Common method bias test, Pearson correlation tests were used to analyses the study indicators and the theoretical model for this study was validated using Process plug-in developed by Hayes and set at p < 0.05 (two- tail) as statistically significant. Results: The levels of physical activity, subjective well-being, and psychological capital were all significantly higher for male students than female students. However, female students had a significantly higher level of mobile phone dependence. As predicted, there was a direct negative correlation between physical activity and mobile phone dependence, and subjective well-being mediated that relationship. Psychological capital moderated the relationship between subjective well-being and mobile phone dependence. It also positively moderated the indirect effect between physical activity and mobile phone dependence via subjective well-being.